2013
DOI: 10.1371/journal.pone.0064814
|View full text |Cite
|
Sign up to set email alerts
|

High Myeloperoxidase Positive Cell Infiltration in Colorectal Cancer Is an Independent Favorable Prognostic Factor

Abstract: BackgroundColorectal cancer (CRC) infiltration by adaptive immune system cells correlates with favorable prognosis. The role of the innate immune system is still debated. Here we addressed the prognostic impact of CRC infiltration by neutrophil granulocytes (NG).MethodsA TMA including healthy mucosa and clinically annotated CRC specimens (n = 1491) was stained with MPO and CD15 specific antibodies. MPO+ and CD15+ positive immune cells were counted by three independent observers. Phenotypic profiles of CRC infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(105 citation statements)
references
References 72 publications
(78 reference statements)
4
99
0
2
Order By: Relevance
“…TMA slides were incubated with primary antibodies specific for CD8, CD16, MPO (18,22,23), and CD66b (clone G10F5, Biolegend). Secondary staining and negative controls were performed as described previously (18,22,23).…”
Section: Ihcmentioning
confidence: 99%
See 2 more Smart Citations
“…TMA slides were incubated with primary antibodies specific for CD8, CD16, MPO (18,22,23), and CD66b (clone G10F5, Biolegend). Secondary staining and negative controls were performed as described previously (18,22,23).…”
Section: Ihcmentioning
confidence: 99%
“…Secondary staining and negative controls were performed as described previously (18,22,23). Colorectal cancer infiltration by cells expressing defined markers was scored by experienced pathologists.…”
Section: Ihcmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a high myeloperoxidase (MPO) + CD15 + cell infiltration representing neutrophils in colorectal carcinoma was found to be an independent favorable prognostic factor [362,363]. Also, the increased presence of CD16 + (FcγRIII) myeloid cells of the monocyte/macrophage lineage that were also positive for CD45, CD33, CD11b, and CD11c, but not CD64 or HLA-DR, was found to be associated with improved survival in patients with colorectal carcinoma [364].…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypesmentioning
confidence: 99%
“…Many studies have found neutrophils to be an independent factor of poor prognosis and promote the growth of distance metastases in CRC 23, 24. However, other studies have revealed that tumor‐infiltrating neutrophils are associated with a better prognosis in CRC and might promote antitumor immunity 22, 25. CD66b was found to be a reliable marker to identify TANs in cancer tissues using immunohistochemistry, including in CRC tissues 17, 19, 22, 24, 26.…”
Section: Introductionmentioning
confidence: 98%